Study on Colloidal Model of Petroleum Residues through the Attraction Potential between Colloids - Long-li Zhang; Guo-hua Yang; Chao-he Yang; Guo-he Que (International Journal of Analytical Chemistry)
The samples of DaGang atmospheric residue (DG-AR), Middle East atmospheric residue (ME-AR), TaHe atmospheric residue (TH-AR), and their thermal reaction samples were chosen for study. All the samples were fractioned into six components separately, including saturates plus light aromatics, heavy aromatics, light resins, middle resins, heavy resins, and asphaltenes. The dielectric permittivity of the solutions of these components was measured, and the dielectric permittivity values of the components can be determined by extrapolation, which increased steadily from saturates plus light aromatics to asphaltenes. Moreover, the Hamaker constants of the components were calculated from their dielectric permittivity values. The Van der Waals attractive potential energy between colloids corresponding to various models could be calculated from the fractional composition and the Hamaker constants of every component. It was assumed that the cores of colloidal particles were formed by asphaltenes and heavy resins mainly; the other fractions acted as dispersion medium. For the three serials of thermal reaction samples, the Van der Waals attraction potential energy between colloids for this kind of model was calculated. For TH-AR thermal reaction samples, the Van der Waals attraction potential energy presented the maximum as thermal reaction is going on, which was near to the end of coke induction period.